Profil Kemampuan Argumentasi Lisan Berbasis Socioscientific Issues Mahasiswa Pendidikan IPA pada Mata Kuliah Mikrobiologi - Annisa Novianti Taufik; Liska Berlian; Atep Iman; Risa Tarisa (PendIPA Journal of Science Education, 2022)
This study aims to determine the profile of students' oral argumentation skills based on Socioscientific Issues in the Microbiology course. This type of research is a descriptive study in order to obtain an overview of the quality of oral arguments of sixth semester students. The sampling technique used was purposive sampling, totaling 37 students of science class 2017. The instruments used were audio recordings and anecdotal notes. The assessment of the quality of students' oral arguments is based on the Toulmin's Argumentation Pattern (TAP) pattern which consists of claim, data, warrant, backing, and rebuttal elements. The results showed that science students had the quality of oral argumentation which was still at level 1 where student arguments only consist of simple claims with opposing claims obtaining a percentage of 12%,, level 2 had a percentage rate of 88% while level 3%, level 4% and level 5% of 0% means scientific argumentation ability science students are still relatively low. This finding will be the basis for researchers to evaluate the learning program that has been applied in the Microbiology course and become the basis for further research related to learning strategies in improving the oral argumentation skills of prospective science teachers.